Financing high-potential entrepreneurship - Ramana Nanda (IZA World of Labor, 2016)
Entrepreneurship is essential to job creation and to productivity growth and therefore is an important matter for government policy. However, policymakers face a difficult challenge because successful growth for a few firms—which cannot easily be identified in advance—is accompanied by widespread failure for most other new firms. Predicting which firms will fail and which will succeed is nearly impossible. Instead of futilely trying to pick winners, governments can play a useful role in facilitating the growth of the most promising firms by setting the conditions for efficient trial-and-error experimentation across firms.
Keywords: L26; G21; G24; 330; entrepreneurial finance; small business finance; high-potential entrepreneurship; banks; venture capital